Revive the Value of Islamic Spirituality for an Anti-Corruption Mentality - Amir Aziz, Ahmad; Ma’ruf; Mahmud, Agus (International Journal of Psychosocial Rehabilitation, 2020)
Corruption is a crime that is difficult to eradicate, although various methods have been used to deal with it, but it has not had much impact. Various approaches have been taken to prevent it, including religious approaches. This paper intends to explore the spiritual values of Islam contained in the teaching of Sufism, a traditional Islamic scientific discipline that has taken root in history. Through library research, this research explores Sufism values from the works of Sufis and also experts who have written their thoughts in books and journals. The results found that Sufism values have significance for solving the problems in modern society, especially in preventing corruption. Corruption behavior arises because of the negligence factor on the existence of God, who is present. By reinforcing the nature of shidiq, a person will be open, honest, and responsible. If it is accompanied by the ethos of zuhud and qana'ah, it will be able to prevent someone from behaving corruptly.